Proteomic identification of galectin-11 and 14 ligands from Haemonchus contortus - Dhanasekaran Sakthivel; Jaclyn Swan; Sarah Preston; MD Shakif-Azam; Pierre Faou; Yaqing Jiao; Rachael Downs; Harinda Rajapaksha; Robin Gasser; David Piedrafita; Travis Beddoe (PeerJ, 2018)
Haemonchus contortus is the most pathogenic nematode of small ruminants. Infection in sheep and goats results in anaemia that decreases animal productivity and can ultimately cause death. The involvement of ruminant-specific galectin-11 (LGALS-11) and galectin-14 (LGALS-14) has been postulated to play important roles in protective immune responses against parasitic infection; however, their ligands are unknown. In the current study, LGALS-11 and LGALS-14 ligands in H. contortus were identified from larval (L4) and adult parasitic stages extracts using immobilised LGALS-11 and LGALS-14 affinity column chromatography and mass spectrometry. Both LGALS-11 and LGALS-14 bound more putative protein targets in the adult stage of H. contortus (43 proteins) when compared to the larval stage (two proteins). Of the 43 proteins identified in the adult stage, 34 and 35 proteins were bound by LGALS-11 and LGALS-14, respectively, with 26 proteins binding to both galectins. Interestingly, hematophagous stage-specific sperm-coating protein and zinc metalloprotease (M13), which are known vaccine candidates, were identified as putative ligands of both LGALS-11 and LGALS-14. The identification of glycoproteins of H. contortus by LGALS-11 and LGALS-14 provide new insights into host-parasite interactions and the potential for developing new interventions.